2002
DOI: 10.5194/hess-6-527-2002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological processes and their seasonal controls in a small Mediterranean mountain catchment in the Pyrenees

Abstract: The Vallcebre catchments are located in a middle mountain area of the Pyrenean ranges, built up by sedimentary rocks and loamy soils. The vegetation cover is pastures and forests of Pinus sylvestris, mostly occupying former agricultural terraces. Some relatively small, heavily eroded landscapes (badlands) occur in the catchments, playing a relevant hydrological and geomorphic role. Annual precipitation is 924 mm and potential (reference) evapotranspiration is about 700 mm. Rainfall interception in forests repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
157
0
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 17 publications
13
157
0
10
Order By: Relevance
“…The complexity in the generation of runoff was also reported for several drainage basins with Mediterranean mountain climate (Gallart et al, 2002;García Ruiz et al, 2005). Llorens and Gallart (1992) and Gallart et al (1994) already showed that the response of these catchments is largely driven by antecedent conditions, demonstrating that during the year, the dominant runoff generation mechanisms change gradually, as a result of both varying catchment antecedent wetness conditions and changing rainfall event characteristics (Gallart et al, 2005).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 93%
“…The complexity in the generation of runoff was also reported for several drainage basins with Mediterranean mountain climate (Gallart et al, 2002;García Ruiz et al, 2005). Llorens and Gallart (1992) and Gallart et al (1994) already showed that the response of these catchments is largely driven by antecedent conditions, demonstrating that during the year, the dominant runoff generation mechanisms change gradually, as a result of both varying catchment antecedent wetness conditions and changing rainfall event characteristics (Gallart et al, 2005).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 93%
“…Climate is sub-Mediterranean, with an average air temperature of 7.3 • C (measured at 1440 m.a.s.l.) and 924 mm of annual rainfall [16]. The present landscape is mainly a mosaic of mesophilous grassland of the Aphyllantion type and Scots pine forests, which colonised old agricultural terraces after their abandonment [37].…”
Section: Study Sitesmentioning
confidence: 99%
“…Beven, 2002). Nevertheless, field studies have shown that overland flow may also be produced in these environments as the result of saturation mechanisms, such as the saturation of thin soils during large events (Martinez-Mena et al, 1998), the seasonal saturation of first order valley bottoms (Ceballos & Schnabel, 1998) or the seasonal formation of a water table and saturated areas throughout the catchment, with relevant contribution from subsurface flow (Gallart et al, 2002;Latron & Gallart, 2007). Hydrological systems are complex, and different hydrologists might not necessarily agree on which are the most important processes in a catchment (Beven, 2002).…”
Section: Introductionmentioning
confidence: 99%